Uporabnost nacionalnih podatkov laserskega skeniranja in cikličnega aerofotografiranja pri zaznavanju gozdnih vrzeli - Pintar, Anže Martin (Geodetski vestnik, 2024)
The forest floor is covered with tree canopy, and the forest canopy gap is a larger or smaller area of the floor that is not covered by the canopy of the dominant tree layer. The size of the gap affects tree species rejuvenation, as well as the vertical and horizontal structure of the forest. In the Pohorje area (Pahernik’s forest estate), which is characterized by forests where trees of different diameters and ages occur in small areas, we analyzed the possibilities of automatic gap detection based on data from the Laser Scanning of Slovenia (LSS) and the Cyclic Aerial Survey of Slovenia (CAS). We used Canopy Height Models (CHM) derived from both data sources. The overall detection accuracy even for the smallest gaps (smaller than 50 m2) was 94.4% based on the LSS data and 83.1% based on the CAS data. A larger number and area of gaps can be detected based on the LSS data, and the gaps derived from the LSS data are more disaggregated and elongated. The detection of gaps with CAS data and LSS data is more comparable with a minimum gap area of 100 m2; the accuracy of detecting such gaps is 85.4 and 94.4 % respectively. The results of the study show that in the absence of LSS data, the use of CAS data to detect forest canopy gaps on a large scale is useful when gaps with an area of more than 100 m2 are detected.
Keywords: canopy height model; cyclic aerial survey of Slovenia; daljinsko zaznavanje; digitalni model krošenj; forest canopy gap; geodezija; gozdovi; laser scanning; laser scanning of Slovenia; lasersko skeniranje; remote sensing; Slovenija; uneven-aged forests